Comparison of early postoperative pain after partial tumour nephrectomy by flank, transabdominal or laparoscopic access. Issue 3 (August 2019) - Hager, Boris; Herzog, Sereina A; Hager, Barbara; Sandner-Kiesling, Andreas; Zigeuner, Richard; Pummer, Karl
Aim: To explore whether the total pain experience differs after (partial) kidney tumour nephrectomies via flank, transabdominal or laparoscopic access. Materials and methods: We analyzed retrospectively 107 patients with flank, 12 with transabdominal and 21 with laparoscopic interventions. For pain treatment, conventional analgesics (A) or intravenous patient-controlled analgesia (PCIA) or thoracic peridural analgesia (tPDA) were used. Self-reported pain was measured with a Visual Analogue Scale three times daily. The area under the curve (AUC) at rest (R) and during a standardized body movement (M) were calculated from the intervention till the end of the second T(0–2) and seventh postoperative day T(0–7), respectively. Results: The median AUC for T(0–2) at R was more intense for laparoscopy (13) than for flank incision (A, 9) and approximately the same during M. For flank incisions (A), the median AUC at R rises from 9 for T(0–2) to 22 for T(0–7) and at M the median AUC increases from 18 to 37. In contrast, laparoscopy did not cause further pain after the second postoperative day. Furthermore, with flank incision for T(0–2), at R, tPDA was superior to A (median AUC: 5 versus 9, p = 0.02) and at M again tPDA (median AUC: 12) had a better pain-control as A (18) or even as PCIA (19, p = 0.005). Conclusion: Laparoscopic nephrectomies cause a relatively intense mean cumulative pain for T(0–2) and a subsequent absence of pain. However, flank incisions went on to increased pain levels until the seventh postoperative day with tPDA as most effective therapy.